경기 화성 지역에서의 스트로브잣나무의 6개 산지별 생장특성 - 최형순(Hyung Soon Choi); 유근옥(Keun Ok Ryu); 현정오(Jung Oh Hyun) (Korean journal of breeding, 2009)
스트로브잣나무의 미국 6개 산지의 생장을 분석한 결과, 남쪽산지인 Georgia와 North Carolina 산지의 생장이 가장 우수하였다. 전체적인 생장의 경향은, 남쪽 산지의 생장이 우수한 반면 북쪽 산지의 생장은 상대적으로 저조하였으며, 잣나무에 비해 평균 2.4배(1.7~3.1배) 정도 재적생장이 우수하였다. 유시생장의 순위가 27년생까지 거의 변하지 않고 유지 되었으며, 이는 우수산지에 대한 조기선발 가능성이 매우 높음을 알 수 있었다. The growth performance of eastern white pine (Pinus strobus L.) was studied with six provenances originated from U.S. in a Hwasong plantation. Height and diameter growth were significantly different among provenances. In general, the growth of southern provenances were larger than that of northern provenances. Georgia and North Carolina provenances proved to be appropriate ones in our plantation, while Minnesota was worst in growth. Annual height growth was still increased at age 27, whereas annual diameter growth was highest at age 11, after that growth rate was gradually decreased. Pearson's correlation among ages was highly positively correlated. The rank of growth has not almost been changed from juvenile stages to at age 27.